NF1 mutations are recurrent in adult acute myeloid leukemia and confer poor outcome. Issue 12 (December 2018) - Eisfeld, Ann-Kathrin; Kohlschmidt, Jessica; Mrózek, Krzysztof; Mims, Alice; Walker, Christopher; Blachly, James; Nicolet, Deedra; Orwick, Shelley; Maharry, Sophia; Carroll, Andrew; Powell, Bayard; Kolitz, Jonathan; et al.
Abstract Targeted mutation assessment of 81 genes in 1021 adults with de novo acute myeloid leukemia (AML) identified recurrent mutations in theneurofibromin 1 (NF1 ) gene in 52 (5.1%) patients, including 36 (5.2%) younger and 16 (4.8%) older patients, which suggestsNF1 belongs to the 20 most frequently mutated genes in adult AML.NF1 mutations were found throughout the gene, and comprised missense, frameshift, and nonsense mutations. One mutation hotspot, at amino acid threonine 676 (Thr676), was found in 27% of AML patients withNF1 mutations.NF1 -mutated patients belonged more often to the adverse European LeukemiaNet (ELN) risk category thanNF1 wild-type patients. Among patients aged <60 years, the presence ofNF1 Thr676 mutations was associated with lower complete remission (CR) rates (P  = 0.04) and shorter overall survival (OS;P  = 0.01), as was the presence of anyNF1 mutation in patients in the adverse ELN risk category (CR, P  = 0.05; OS, P  < 0.001). CR rates were also lower inNF1 -mutated patients aged ≥60 years compared withNF1 wild-type patients (P  = 0.001). In summary, our findings provide novel insights into the frequency ofNF1 mutations in AML, and are suggestive of an adverse prognostic impact in patients treated with standard chemotherapy.